Tinjauan Kritis terhadap Absennya Hak Preferen Korban pada Eksekusi Barang Bukti Hasil Kejahatan (Proceeds Of Crime) dalam Sistem Peradilan Pidana Baru - Tommy Marly Mandagi; Yusrianto Kadir; Ramdhan Kasim (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2026)
This research is motivated by legal problems wherein victims of crimes often fail to receive actual economic recovery, despite court decisions having obtained permanent legal force. The problem becomes increasingly difficult when the defendant experiences insolvency (inability to pay) or when the proceeds of crime are instead forfeited to the state. This study aims to construct a just mechanism for the execution of evidence by granting Preferential Rights to victims over the rights of the state and other creditors. The research method employed is normative legal research using a statutory approach, a conceptual approach, and a comparative approach. The theoretical framework utilized consists of John Locke's Theory of State Moral Obligation, Richard Posner's Economic Analysis of Law, and Guido Calabresi's concept of Loss Alleviation. The results indicate that the absence of Preferential Rights regulations in both the New Criminal Code (KUHP Baru) and the New Criminal Procedure Code (KUHAP Baru) causes legal uncertainty and economic inefficiency that harms victims (secondary costs). This thesis offers a legal reform idea in the form of applying